2016
DOI: 10.1016/j.amsu.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Effective, simple, easy procedure for laparoscopic port closure in difficult cases

Abstract: BackgroundLaparoscopic and rebotic surgery is widely practiced in modern medicine. The operative procedure is not complete until the port sites are closed with a fascial closure. Good fascial closure still represents problem, especially in difficult obese patients. This study reported simple technique is suitable in such cases.Material and methodsWe herein describe a simple technique for fascial closure after Laparoscopic surgery using percutaneous transabdominal approach by using two looped needles in 87 obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, all these procedures are unsuitable in obese cases because of the thick abdominal wall and oblique wound necessitating assistance from inside; the suture is placed from the port site, which requires an increased skin incision, and the suture passes close to the edges of the fascia defect. Lasheen et al reported percutaneous transabdominal technique for closure of the port site with no port site herniation [ 10 , 11 ]. However, this technique cannot be used in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all these procedures are unsuitable in obese cases because of the thick abdominal wall and oblique wound necessitating assistance from inside; the suture is placed from the port site, which requires an increased skin incision, and the suture passes close to the edges of the fascia defect. Lasheen et al reported percutaneous transabdominal technique for closure of the port site with no port site herniation [ 10 , 11 ]. However, this technique cannot be used in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that laparoscopic port site hernias can occur with incisions as small as 3 mm [ 8 ]. It is recommended that the fascia of 10 mm or wider trocar sites in adults and 5 mm or wider port sites in children must be closed [ 9 11 ]. Complete closure of fascia at the port site can be complicated and frustrating, often requiring blind suturing of the fascial defect, with the risks of incomplete closure and injury to the intraperitoneal organs or larger skin incisions.…”
Section: Introductionmentioning
confidence: 99%
“…19 • Ports which are 10 mm and higher, either midline or lateral, must be closed at the level of fascia. 29,56 • The use of minimal necessary ports. Neudecker et al…”
Section: Whether To Close or Notmentioning
confidence: 99%